Mapeamento de Paleosuperfícies associadas a identificação de depósitos supérgenos de cobre como ferramenta de exploração mineral na região de Itapeva e Ribeirão Branco- Vale do Ribeira, estado de São Paulo, Brasil - Ribeiro, Luiz Felipe Brandini [UNESP] (2010)
A few examples of supergene ore formation and their interaction with morphogenesis (palaeosurfaces) and weathering mineralogy are discussed. Geomorphological and mineralogical records to characterize palaeosurfaces associate the weathering of primary minerals and their relationship with concentrations of cooper and iron ore deposits in southeastern state of São Paulo, Brazil. We have distinguished two palaeosurfaces generated by several weathering phases and controlled by the geological framework. The first and oldest upper palaeosurfaces (900 - 1000 m a.s.l.), situated in Riberão Branco (Alto do Brancal), were developed on silico-limestones. It is formed by typical iron laterites enriched by secondary products of cooper. The second and younger level palaeosurfaces located in Itapeva (Santa Blandina and Bairro do Sambra). This palaeosurface is formed by copper percolating through the weathered rock (saprolite). Other features can be observed like neo-formed products in laterites. They are classified into two types: clay like silico- cupriferous products (with noticeable amounts of iron) and copper minerals (crysocolla, in their flat slopes). These features allowed the presence of copper ores and their morphogenesis control will help in the exploration and prospecting of supergene ore mineral.